VILLAGE-OWNED ENTERPRISES IN BREBES REGENCY: GOVERNANCE GAPS, MARKET COMPETITION, AND PATHWAYS TO SUSTAINABILITY - Pratysto, Tangguh; Fransiscus Xaverius Sugiyanto; Deny Cahyadinanto Sanjoko; Maulana Ghani Yusuf; Moh Najikhul Fajri (Journal of Islamic Economy and Community Engagement, 2025)
The poverty rate in Brebes is among the highest in the province, with 15.6% of its people living below the poverty line in 2024. To overcome these problems, Village-owned Enterprises (BUM Desa) were introduced through Law No. 6 of 2014 to tap local potential, boost welfare, and raise Village Original Revenue. While every village in Brebes has a BUM Desa, many are still at the beginning of their development and experience setbacks in areas such as legal formalisation, governance, managerial skills, and market competitiveness. This research uses a qualitative approach and a semi-structured interview with the Baperlitbangda and Dinpermades to analyse the institution's performance and its relationship with the emerging Koperasi Desa Merah Putih (KDMP). The findings indicate reliance on individual leadership, high levels of non-performing loans, and unclear market-share allocations, as Village-Owned Enterprises (BUMDes) are suspected of competing with KDMPs rather than collaborating with them. Strengthening the legal framework for professional management of Village-Owned Enterprises (BUM Desa) in Brebes Regency is necessary to realize a dynamic village economy.